Level of knowledge and awareness of catering students at UTHM towards G6PD - Harun, Hairuddin; Mohd Nasruddin, Muhammad Azri Hadi (Penerbit UTHM, 2021)
Most food trends nowadays refer to seafood and foods that are gaining popularity on social media. According to (Khairani, 2018) the desire arises from the followers of social sites such as Instagram because they are attracted to what is offered through the marketing process. This suggests that the public is now more open to accepting new food products in the market or simply through the promotion of social media space especially food that is viral nowadays. Food allergy to peanuts is one of the most commonly reported causes of child abuse, affecting 3% of children and continuing in adults in up to 80% of cases (Al, 2015). Peanut allergy is a body's immune response that is considered to be an unwanted foreign substance. The 2010 and 2015 guidelines for the prevention of peanut allergy in the United States do not provide an allergy prevention recommendation due to a lack of supporting evidence (Togies et al., 2017). Therefore, the family was instructed to recognize the early symptoms of allergy and take epinephrine injections at all times for early treatment before it gets worse.